Alginate/porous silica matrices for the encapsulation of living organisms: tunable properties for biosensors, modular bioreactors, and bioremediation devices - Perullini, Ana Mercedes (2015)
The encapsulation of living cells within inorganic silica hydrogels is a promising strategy for the design of biosensors, modular bioreactors, and bioremediation devices, among other interesting applications, attracting scientific and technological interest. These host-guest multifunctional materials (HGFM) combine synergistically specific biologic functions of their guest with those of the host matrix enhancing their performance. Although inorganic immobilization hosts present several advantages over their (bio)polymer-based counterparts in terms of chemical and physical stability, the direct contact of cells with silica precursors during synthesis and the constraints imposed by the inorganic host during operating conditions have proved to influence their biological response. Recently we proposed an alternative two-step procedure including a pre-encapsulation in biocompatible polymers such as alginates in order to confer protection to the biological guest during the inorganic and more cytotoxic synthesis. By means of this procedure, whole cultures of microorganisms remain confined in small liquid volumes generated inside the inorganic host, providing near conventional liquid culture conditions. Moreover, the fact of protecting the biological guest during the synthesis of the host, allows extending the synthesis parameters beyond biocompatible conditions, tuning the microstructure of the matrix. In turn, the microstructure (porosity at the nanoscale, radius of gyration of particles composing the structure, and fractal dimension of particle clusters) is determinant of macroscopic parameters, such as optical quality and transport properties that govern the encapsulation material´s performance. Here we review the most interesting applications of the two-step procedure, making special emphasis on the optimization of optical, transport and mechanical properties of the host as well as in the interaction with the guest during operation conditions.